2008
DOI: 10.2214/ajr.07.3665
|View full text |Cite
|
Sign up to set email alerts
|

Low Injection Rate for 3D Moving-Table Bolus-Chase MR Angiography: Initial Experience with 3-T Imaging to Allay Venous Contamination in the Calf

Abstract: At 3-T MRI, a lower injection rate may alleviate venous contamination and increase arterial visibility in the calf while signal-to-noise and contrast-to-noise ratios at higher levels are maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Using B-mode ultrasound, El-Magadmi et al showed impaired flow-mediated dilation (FMD, representing endothelial dysfunction) in the brachial artery and increased carotid intima-media thickness (IMT, an indicator of atherosclerosis) in female SLE patients (n = 62) 75 . In clinical practice, CTA and MRA are the standard-of-care for the detection of lumen stenosis in peripheral arteries 76, 77 .…”
Section: Peripheral Artery Disease (Pad)mentioning
confidence: 99%
See 2 more Smart Citations
“…Using B-mode ultrasound, El-Magadmi et al showed impaired flow-mediated dilation (FMD, representing endothelial dysfunction) in the brachial artery and increased carotid intima-media thickness (IMT, an indicator of atherosclerosis) in female SLE patients (n = 62) 75 . In clinical practice, CTA and MRA are the standard-of-care for the detection of lumen stenosis in peripheral arteries 76, 77 .…”
Section: Peripheral Artery Disease (Pad)mentioning
confidence: 99%
“…76 In clinical practice, CTA and MRA are the standard of care for the detection of lumen stenosis in peripheral arteries. 77,78 Pericarditis Nearly 40% of SLE patients have acute and chronic inflammatory pericardial changes and most of them are asymptomatic individuals. 2 It is usually not considered as a life-threatening complication.…”
Section: Peripheral Artery Disease (Pad)mentioning
confidence: 99%
See 1 more Smart Citation